SALURAN ILMU MENURUT IBNU TAIMIYAH DAN RELEVANSINYA DENGAN PEMBAHARUAN PEMIKIRAN ISLAM DI ERA POST-TRUTH - Iskandar; Samsuddin; Maya, Rahendra; Agusman (JURNAL KAJIAN ISLAM MODERN, 2024)
ABSTRACT The purposes of this research were to analyze and describe the concept of knowledge transmission according to Ibn Taimiyah. This research is a type of library research using descriptive qualitative methods with a historical and philosophical approach. The results of this research show that there are three transmissions and channels of knowledge in Ibn Taimiyah's perspective: revelation (wahyu), reason, and the senses. There is no conflict between the three. However, revelation is the absolute and main channel of knowledge. while reason and senses are channels of knowledge that must be subject to revelation. Both play a role in digesting and understanding the truth that comes from revelation. Keyword: Knowledge transmission, ibn taimiyah, knowledge phylosphy